2020
DOI: 10.5604/01.3001.0014.4136
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgery for giant cell tumors of the tendon sheath within the hand.

Abstract: Giant cell tumor of the tendon sheath is the most common benign proliferative lesion involving the upper limb, characterised by relatively high recurrence rate after surgery. The objective of the study was a retrospective analysis of outcomes of the operative treatment of these tumours, in a long-term (a mean of 4,2 year) follow-up. Patients and methods. Preoperative examination was performed in 58 patients, 36 females (62%) and 22 males (38%), in a mean age of 41 years, and treatment outcomes were assessed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…GCTTS can cause cortical bone erosions and invasion of the medullary space, which can be seen on plain radiographs [ 2 , 6 ]. Plain radiographs of the hand and wrist show the bony structures and cannot visualize a ganglion cyst as such [ 7 ]. Magnetic resonance imaging is a useful diagnostic imaging modality for the classification of GCTTS into Al Qattan types 1 and 2 [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCTTS can cause cortical bone erosions and invasion of the medullary space, which can be seen on plain radiographs [ 2 , 6 ]. Plain radiographs of the hand and wrist show the bony structures and cannot visualize a ganglion cyst as such [ 7 ]. Magnetic resonance imaging is a useful diagnostic imaging modality for the classification of GCTTS into Al Qattan types 1 and 2 [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to what happened in this index patient; the lesion was earlier excised four years prior, and the lesion had now recurred. Incomplete surgical excision is widely accepted as a definitive risk factor [ 7 ]. Other known risk factors for local recurrence include the presence of adjacent degenerative joint disease, localization at the distal interphalangeal joint of the fingers or thumb, cortical destruction, type 2 tumors, increased cellularity and mitotic activity, and neurovascular dissection during removal [ 1 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are suggestions that neoplasm may be connected with chromosomal aberrations, mostly regarding chromosome 22. [7,8]. Rarely, schwannomas transform into malignant peripheral nerve sheath tumours, and up to 50% of malignancy events are connected with neurofibromatosis [1,5].…”
Section: Methodsmentioning
confidence: 99%
“…The ulnar nerve tends to be the most common location [9]. The upper limb is affected in approximately 19% of cases [6,8]. Intraosseous schwannoma of limbs is rare, although there are case studies in literature describing this type of neoplasm in the upper limb.…”
Section: Selected Cases Of Intraosseous Schwannoma In Upper Limbmentioning
confidence: 99%
“…Schwannomas grow inside the nerve, causing thickening of the nerve. As the tumor is encapsulated the nerve bundles do not penetrate it, but intertwist it, which allows enucleation of the tumor [9]. There is no studies that showed the surgical outcomes after excision of isolated BPNSTs without neurofibromatosis, especially in long follow up period.…”
Section: Introductionmentioning
confidence: 99%